1997
DOI: 10.3168/jds.s0022-0302(97)76024-7
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Health and Disorders

Abstract: Nonspecific uterine infections reduce the reproductive efficiency of cows and the profit potential of dairy farms. Fortunately, most cows do not develop severe uterine infections. The term uterine infection indicates that the uterus is contaminated with pathogenic organisms. Actinomyces pyogenes, either alone or with other bacteria, is often associated with uterine infections. When A. pyogenes was isolated from uterine fluids after d 21 postpartum, cows developed severe endometritis and were infertile at first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
1
18

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(173 citation statements)
references
References 48 publications
6
148
1
18
Order By: Relevance
“…Most of these bacterial contaminations get eliminated during the first 5 weeks after parturition, but the remaining causes the uterine infection in some cows (Noakes et al, 2009;Sheldon et al, 2006). Common bacteria isolated from cows with uterine infections are Trueperella pyogenes, Prevotella sp., Fusobacterium necrophorum and Escherichia coli (Sheldon et al, 2006;Lewis, 1997;Smith et al, 1998;Overton et al, 2003and Sheldon et al, 2004.…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 1769-1775mentioning
confidence: 99%
“…Most of these bacterial contaminations get eliminated during the first 5 weeks after parturition, but the remaining causes the uterine infection in some cows (Noakes et al, 2009;Sheldon et al, 2006). Common bacteria isolated from cows with uterine infections are Trueperella pyogenes, Prevotella sp., Fusobacterium necrophorum and Escherichia coli (Sheldon et al, 2006;Lewis, 1997;Smith et al, 1998;Overton et al, 2003and Sheldon et al, 2004.…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 1769-1775mentioning
confidence: 99%
“…Un hallazgo importante de las infecciones bacterianas es su relación con el estado endocrino del animal, así bajo el predominio de la progesterona se suprime los mecanismos de defensa uterina, por lo tanto la formación del primer cuerpo lúteo después del parto y la secreción de progesterona anteceden la presencia de enfermedad uterina (Lewis 1997;2004). Es necesario aclarar que en el presente estudio, se evidenció la presencia de infección uterina, más no la presencia de enfermedad uterina la cual no estaba dentro de los propósitos del mismo.…”
Section: Discussionunclassified
“…Sheldon et al (2009) identified the most prevalent bacteria as Arcanobacterium pyogenes, Escherichia coli, Fusobacterium necrophorum, Prevotella melaninogenica and Proteus species but found no interaction between the pathogenic group present and the severity of intrauterine infection. Arcanobacterium pyogenes, now reclassified as Trueperella pyogenes (Yassin et al 2011), is an opportunistic pathogen of domestic ruminants and, either alone or with other bacteria, is commonly associated with bovine uterine infections (Griffin et al 1974;Lewis 1997). Repeated postpartum uterine sampling showed that T. pyogenes was the most common bacterial species isolated between 8 and 42 days postpartum (DPP) and was the most prevalent organism isolated in cows with severe endometritis (69% of severe cases); however, it was extremely rare after 21 DPP in cows that conceived to first service (Williams et al 2005).…”
Section: Introductionmentioning
confidence: 99%